Engagement in Agriculture Protects Against Food Insecurity and Malnutrition in Peri-Urban Nepal. Issue 1 (1st November 2018) - Moucheraud, Corrina; Chandyo, Ram K; Henjum, Sigrun; Strand, Tor A; Ulak, Manjeswori; Fawzi, Wafaie W; Locks, Lindsey M; Webb, Patrick; Thorne-Lyman, Andrew L
Abstract: Background: Urbanization is occurring rapidly in many low- and middle-income countries, which may affect households' livelihoods, diet, and food security and nutritional outcomes. Objective: The main objective of our study was to explore whether agricultural activity among a peri-urban population in Nepal was associated with better or worse food household security, household and maternal dietary diversity, and nutritional outcomes for children and women. Methods: A cross-sectional survey was administered to 344 mother–child pairs in Bhaktapur district, Nepal, including data on household agricultural practices, livestock ownership, food security, dietary diversity and expenditures, anthropometric measurements of children (aged 5–6 y), maternal body mass index (BMI), and maternal anemia. Multivariable adjusted odds ratios (AORs) and unadjusted odds ratios were calculated using logistic regression. Results: Our findings suggest that in this sample, cultivation of land was associated with lower odds of child stunting (AOR: 0.55; 95% CI: 0.33, 0.93) and household food insecurity (AOR: 0.33; 95% CI: 0.18, 0.63), but not low (or high) maternal BMI or anemia. Livestock ownership (mostly chickens) was associated with lower food insecurity (AOR: 0.34; 95% CI: 0.16, 0.73) but not with nutrition outcomes. Women in farming households were significantly more likely to eat green leafy vegetables than were women in nonfarming households, and children living in households that grew vegetables had a lower odds of stunting than children in households that cultivated land but did not grow vegetables (AOR: 0.49; 95% CI: 0.25, 0.98). Conclusions: Our study suggests that households involved in cultivation of land in peri-urban Bhaktapur had lower odds of children's stunting and of food insecurity than noncultivating households, and that vegetable consumption is higher among those households. Given Nepal's rapid urbanization rate, more attention is needed on the potential role of peri-urban agriculture in shaping diets and nutrition.